An annotated catalogue of the lichen forming fungi of the Yalta Mountain-Forest Nature Reserve (CHORNOMORSKI BOTANICAL JOURNAL, 2024)
The list of the lichen forming fungi of the Yalta Mountain-Forest Nature Reserve (AR Crimea, Ukraine) are included 335 species of 105 genera, 42 families, 12 orders. Among them 59 species – new for reserve, 13 – new for Crimea peninsula. The species Lecidea hypoptoides (Nyl.) Nyl., Micarea globulosella (Nyl.) Coppins, Protoparmelia oleagina (Harm.) Coppins, Solenopsora grisea (Bagl.) Kotlov, S. marina (Zahlbr.) Zahlbr. are reported for the fist time for Ukraine. The lichen ecology and locations are reported.
Keywords: lichens, list, Yalta Mountain-Forest Nature Reserve, Crimea.